Great Purple Hairstreak; Great Blue Hairstreak, Atlides halesus (Cramer) (Insecta: Lepidoptera: Lycaenidae) - Donald W. Hall; Jerry F. Butler (EDIS)
The great purple hairstreak, Atlides halesus (Cramer), is one of our most beautiful southern butterflies. Although it is most commonly known as the great purple hairstreak, it has no purple on it. The brilliant iridescent scales on the upper surface of the wings from which it gets its name are blue, not purple. This document is EENY-110, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 1999.